The Dynamics of Winter Wheat Production and Analysis of the Main Affecting Factors in the Regions of the RA in 1991-2020 - Aleksanyan, V. S.; Keshishyan, G. H.; Shirokov, S. N.; Trushkina, I. R. (ՀԱԱՀ հիմնադրամ)
The main goal of the current research is to study development tendencies of winter wheat production in the period of 1991-2020 and to examine the effect of the changes in cropland areas and yield capacity per hectare on the gross yield of winter wheat in separate periods. In 1991-2005, the gross yield demonstrated extensive (quantitative) growth, and in 2006-2016, it was characterized by intensive (qualitative) growth. In 2017-2020, the yield capacity per hectare decreased almost in all marzes of the RA. As a result, the gross yield of winter wheat annually decreased by 13.54 thousand tons in the mentioned subperiod.
Keywords: Agricultural Economics and Agribusiness